A Regularization Process for Electrical Impedance Equation Employing Pseudoanalytic Function Theory. (7th December 2014) - Robles Gonzalez, Cesar Marco Antonio; Bucio Ramirez, Ariana Guadalupe; Ponomaryov, Volodymyr; Ramirez Tachiquin, Marco Pedro
Abstract : The electrical impedance equation is considered an ill-posed problem where the solution to the forward problem is more easy to achieve than the inverse problem. This work tries to improve convergence in the forward problem method, where the Pseudoanalytic Function Theory by means of the Taylor series in formal powers is used, incorporating a regularization method to make a solution more stable and to obtain better convergence. In addition, we include a comparison between the designed algorithms that perform proposed method with and without a regularization process and the autoadjustment parameter for this regularization process.